MENINGKATAN HASIL BELAJAR SISWA KELAS VIIIB MUHAMMADIYAH 1 MAKASSAR MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING - Andi Husniati (Universitas Muhammadiyah Makassar, 2010)
This researchis constituted by fact, that students’ mathematics achievement is still lower and learning model still predominated by lecture. Result of research show student’s achievement complete by using Snowball throwing cooverative model siclus I mean score equal 64,55 by deviation standart 29,18 improvement in siclus II with mean score 81,43 by deviation standart 18,31.